Magneto-structural and photocatalytic behavior of mixed Ni–Zn nano-spinel ferrites: visible light-enabled active photodegradation of rhodamine B - Jadhav, Swapnil A.; Somvanshi, Sandeep B.; Khedkar, Mangesh V.; Patade, Supriya R.; Jadhav, K. M. (Journal of materials science. Materials in electronics, 2020)
The present study compiles with the physicochemical, magnetic, and photocatalytic evaluation of the mixed spinel Ni–Zn nanoferrites prepared by the auto-combustion sol–gel route. All the samples were characterized by XRD for the recognition of phase-pure cubic spinel structure. Spectral studies that were carried out by FT-IR clearly show two absorptions band revealing the characteristics of ferrite skeleton. The morphology of the prepared nanoparticles was visualized by SEM and TEM microscopy technique. BET analysis showed the enhancement in surface parameters. Hydrodynamic diameter and dispersion studies were evaluated by DLS and Zeta potential measurements. The DC resistivity measured by two-probe technique shows the semiconductor behavior for all the samples. M–H hysteresis loop of all the samples exhibited the superparamagnetic behavior. The energy bandgap values obtained by the UV–Vis spectroscopy technique show the increasing trend from 1.82 to 2.07 eV with increase in Ni 2+ content. The photocatalytic activity of Rhodamine B was evaluated under sunlight irradiation. With increasing Ni 2+ concentration, the degradation efficiency increased to 98%. Further, the present nanocatalyst shows active reusability and can be easily separable due to its magnetic nature. The obtained results show the enhanced photocatalytic of the Ni–Zn nanoferrites under the visible light in contrast with the available literature reports.